The Art of Knowledge Exchange : A Results-Focused Planning Guide for Development Practitioners - Kumar, Shobha (World Bank, Washington, DC, 2012)
Knowledge exchange, or peer-to-peer learning, is a powerful way to share, replicate, and scale up what works in development. Development practitioners want to learn from the practical experience of others who have gone through, or are going through, similar problems. This guide emphasizes empowering local agents through experiential learning with peers from their own and other countries, by following a strategic, results-oriented approach to learning based on the World Bank institute's capacity development and results framework. Knowledge exchange can be used as part of a change process to powerful effect. But like any good capacity building approach, it should be anchored in the broader development context and your clients' needs should drive the agenda. The development goal focuses on the major objective your clients hope to achieve. It derives from a long-term regional, national, or local development strategy. The knowledge exchange initiative should bring your clients closer to realizing this goal, by targeting the institutional constraints preventing its achievement. The development goal therefore guides the design of your knowledge exchange. An effective development goal is locally owned and provides clear economic and social value to targeted beneficiaries. It's important to recognize that a knowledge exchange initiative will not result in the development goal, but should contribute to it. In some instances, knowledge exchange can be used to build group consensus on a development goal itself.